The Role of Auditor Ethics as Moderating Variable in Relationship Between Auditor Accountability and Quality of the Audit - Abdul Manap; Rini Yulia Sasmiyati; Norman Edy; Lilik Swarta Angga Buana; Yoesoep Edhie Rachmad (Jurnal EMT KITA, 2023)
This study aims to investigate how the independence and accountability of auditors affect audit quality governed by auditor ethics. This study used primary data collected by distributing questionnaires to 124 KAP auditors in the DKI Jakarta area. The sampling technique used is convenience sampling. Multiple regression analysis and moderate regression analysis are used to analyze the data using SPSS 25 software. The results show that audit quality is influenced by independence and accountability. In addition, auditor ethics can also control the impact of independence on audit quality. However, the impact of accountability does not have a significant effect on audit quality. This research provides a better understanding of the factors that affect audit quality, and underscores the importance of auditor independence and ethics in ensuring better audit quality.